Tinjauan Kasus Cyber Phising 16 Shop Berdasarkan UU ITE Nomor 19 Tahun 2016 - Permata, Azzahra Ayu Nur; Ratnawati, Elfrida (Universitas Ekasakti, 2023)
This study discusses the case of cyber phishing carried out by the phishing Group 16 Shop, namely fraud by creating and selling fake website and software platforms resembling genuine electronic transaction sites for the purpose of deceiving targets. has the ITE Law Number 19 of 2016 been effectively implemented by the government to protect victims and enforce laws related to Cyber Phishing crimes? Is the principal problem of writing this study. The research method used in this study is normative legal research that connects various sources of legal material and is analyzed descriptively. This study aims to analyze the case of “Cyber Phishing 16 Shop” associated with ITE Law Number 19 of 2016 in the role of regulating and protecting cybercriminals related to electronic transactions